In vivo (in)stability shoulder assessment in healthy active adults using force plates and a motion capture system: a cross-sectional study - Ramírez-Pérez, L.; Su, E. Y.-S.; Cuesta-Vargas, A. I.; Kerr, G. K. (Sensors, 2025)
The assessment of shoulder stability is a great challenge in sports medicine. There is a lack of objective tools to assess functional shoulder stability in sports with high demands on the upper limb. This cross-sectional study recruited twenty healthy adults to analyze the use of a force platform in a push-up analysis as a valid tool for estimating glenohumeral stability. For this purpose, the subjects performed one strength task based on a maximum lateral abduction against a dynamometer. They also performed three variations of a push-up task on force plates with movements recorded by a 3D motion capture system. The results showed that healthy adults present similar movement patterns during push-ups, without differences in terms of stability between sexes, although males showed greater values in lateral abduction strength (left: 63.2 vs. 36.8; p < 0.001; right: 64.2 vs. 38.9; p < 0.001) and ground reaction force peak in the three push-up tasks (p < 0.005). Moreover, four prediction models were developed based on the use of force plate data to estimate kinematics concerning humerus acceleration (p < 0.001). In conclusion, this research demonstrated that force plates are a valid tool for upper-limb assessment with significant correlations with dynamometer and 3D motion capture measures.